Maxillar Neurofibroma. A Case Presentation. - Ángel Luis Cruz Leiva; Orlando Sotolongo Terry; Blas Jorge González Manso (Medisur)
A case of a 34 year-old patient who presented a relapsing maxillar neurofibroma of great dimensions is presented. At the time of removing the neurofibroma a bone block including the teeth from # 11 up to # 25 were resected. The surgical treatment was carried out in an ambulatory way using local anesthesia only. This case report may contribute to achieve the trends and levels at present in surgery worldwide, where ambulatory surgery are more numerous nowadays.